Posthumous personhood and the affordances of digital media. - Meese, James; Nansen, Bjorn; Kohn, Tamara; Arnold, Michael; Gibbs, Martin (Mortality, 2015)
This article identifies and outlines some of the more prominent ways that digital media can extend one’s personhood following death. We consider three examples: when the digital persona of the deceased continues to interact with the living through a human surrogate; the emergence of autonomous and semi-autonomous software enabling the dead to use social media to intervene in current events; and finally the operation of algorithmic presence services like Eterni.me, where artificial intelligence creates a re-enlivened form of the deceased. Situating these examples in relation to sociological, anthropological and cultural literature foundational to ideas of distributed personhood and posthumous symbolic immortality, we suggest that digital codes and computational texts stand as key sites for contemporary forms of ‘distributed personhood’, including posthumous personhood. We then extend this body of literature by examining how the discursive politics of social media contributes to a social and commercial context, which supports ongoing interactions with the dead online. Through this process, we suggest that the persona of the dead, which remains after bodily death, can continue to maintain meaningful posthumous relationships with the living, presenting a new perspective on how we interact with the dead through digital media.